1998
DOI: 10.1002/1529-0131(199803)41:3<482::aid-art15>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of the human T cell receptor ? chain in juvenile rheumatoid arthritis and juvenile spondylarthropathies: Evidence for antigenic selection of T cells in the synovium

Abstract: Objective. To identify features of the T cell receptors (TCRs) present on clonally expanded T cells in the joints of patients with similar types of childhood rheumatic disease. V,8 and V,20 TCRs were selected as prototypic for polyarticular juvenile rheumatoid arthritis (JRA) and pauciarticular/juvenile spondylarthropathy (SPA), respectively. Methods.The portion of the TCR p chain involved in antigen recognition in the synovial tissue, synovial fluid, and peripheral blood from patients with JRA and juvenile SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…This finding may be explained by the reactivity of the same T cell populations to homologous peptides of either microbial or self origin (35,36). Further analysis of these T cell populations by means of a novel method, TCC, for the identification of rare antigen-specific T cells (30), showed oligoclonality of these T cell populations with largely overlapping TCR V ␤ genes.…”
Section: Discussionmentioning
confidence: 98%
“…This finding may be explained by the reactivity of the same T cell populations to homologous peptides of either microbial or self origin (35,36). Further analysis of these T cell populations by means of a novel method, TCC, for the identification of rare antigen-specific T cells (30), showed oligoclonality of these T cell populations with largely overlapping TCR V ␤ genes.…”
Section: Discussionmentioning
confidence: 98%
“…A similar sequence of events could take place in the synovia of children with JIA. In fact, as previously reported [15], the evaluation of the molecular organization of the TCR revealed that T cells proliferating in children with JIA show a preferential usage of definite TCR gene regions, indicating an ordered immune response in which a specific TCR has been triggered and CXCR3 expression is induced [16]. …”
Section: Discussionmentioning
confidence: 59%
“…(52) Synovial fluid samples from patients with different JIA subtypes show markedly different CD4 / CD8 ratios, (53) proportions of activated CD4 and CD8 T cells, (53) degrees of clonal expansion, (54) associated HLA-DR B1 loci, and involvement of Vβ families among the highly oligoclonally expanded T cells. (55) These findings suggest that different autoantigens may be involved in different JIA subtypes. Yao et al reported mutation of the RANTES gene promoter in patients with JIA and this mutation was associated with increased RANTES secretion and synovial membrane inflammation.…”
Section: Pathogenesismentioning
confidence: 87%